Design of an intelligent sensor network for distributed energy system - Putt, Kar Yuan. (2009)
A sensor network with intelligent behavior is a system that can adapt to the situation, present information that is relevant for the moment and a system that has reasoning parts that are designed to function with low-level rules and work together to accomplish a high-level goal. A distributed energy system normally consists of a number of small-scale distributed energy sources, such as micro-turbines, fuel cells and solar photovoltaics, to produce electric power at locations near to customers.